The Indic Perspective of the Pro-democracy Agitation (2020) in Thailand - Samant, Pulind (ASIAN REVIEW, 2021)
The current agitation in Thailand can be interpreted differently in India than it may be viewed by the world. The reason is the attack on the Thai monarchy launched by the agitators in the midst of their demands. The Thai monarchy is not only the strongest pillar of the Thai identity, but also the symbol of its Indic civilisational roots, through institutionalization of the title Rama. There is a long history of attack on the institution of monarchy elsewhere in the South East Asia region, where a pattern of fall of royalty followed by subsequent weakening of the state can be observed. From the region, Thailand can be considered as culturally closest to India. Even from the geo-strategic angle, it is an important player for India in its extended neighborhood. India is therefore right in feeling concerned about the said agitation and the future course it might take.